Pertumbuhan dan Perkembangan Ubi Kayu Genotipe Lokal Manggu pada Panjang Setek Batang yang Berbeda - Nurul Khumaida; Siswati, Leni; Ardie, Sintho Wahyuning (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2019)
Cassava plant is widely cultivated by Indonesian people. Research on the development of roots and tubers of cassava is still limited. The purpose of this study was to evaluate the effect of stem cut size on the root development system and tuber filling in the cassava local genotype “Manggu”. This study consisted of two experiments namely experiments in polybag and in the field. The study was conducted in the IPB experimental field at Cikabayan in December 2017-July 2018. The experiment used a randomized completely block design (RCBD) with two treatments and three replications, namely cuttings of 15 cm and 30 cm. Observation of basal roots, number of nodal roots, length of basal roots, length of nodal roots, number of tubers, number of leaves, plant diameter, and plant height were carried out destructively every week. The results showed that the root bulking process occurred in the nodal root and basal roots and it was observed since 5 WAP. The results showed a positive correlation between the total number of tubers and the number of tubers formed from nodal and basal roots, the number of basal roots, and the length of basal roots and it was negatively correlated with the number of leaves. The number of tubers from nodal roots is positively correlated with the number of basal root tubers while it is negatively correlated with the length of the nodal root. The development of roots into cassava tubers occurred since 5 WAP. Cutting size treatments significantly did not affect root development. Keywords: basal root, nodal root, stem cutting, stem length